2004
DOI: 10.1074/jbc.m309280200
|View full text |Cite
|
Sign up to set email alerts
|

Human Hepatitis B Virus-X Protein Alters Mitochondrial Function and Physiology in Human Liver Cells

Abstract: The hepatitis B virus-X protein (HBx) regulates fundamental aspects of mitochondrial physiology. We show that HBx down-regulates mitochondrial enzymes involved in electron transport in oxidative phosphorylation (complexes I, III, IV, and V) and sensitizes the mitochondrial membrane potential in a hepatoma cell line. HBx also increases the level of mitochondrial reactive oxygen species and lipid peroxide production. HBx does not activate apoptotic signaling, although it sensitizes hepatoma cells to apoptotic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
141
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(146 citation statements)
references
References 44 publications
5
141
0
Order By: Relevance
“…In contrast, a recent report based on proteomic analysis revealed that proteasome subunits were upregulated in tumor liver tissues in HBx p21 knockin transgenic mice (Cui et al, 2006). HBx exerts powerful effects on mitochondria either directly owing to their channel-forming activity or indirectly through interactions with endogenous channels (Takada et al, 1999;Henkler et al, 2001;Lee et al, 2004). HBx reportedly interacts with at least two mitochondrial proteins, namely heat-shock protein 60 and 70 (Tanaka et al, 2004;Zhang et al, 2005b) and the VDAC isoform VDAC3 (Rahmani et al, 2000;Kim, 2005).…”
Section: Hbxmentioning
confidence: 95%
“…In contrast, a recent report based on proteomic analysis revealed that proteasome subunits were upregulated in tumor liver tissues in HBx p21 knockin transgenic mice (Cui et al, 2006). HBx exerts powerful effects on mitochondria either directly owing to their channel-forming activity or indirectly through interactions with endogenous channels (Takada et al, 1999;Henkler et al, 2001;Lee et al, 2004). HBx reportedly interacts with at least two mitochondrial proteins, namely heat-shock protein 60 and 70 (Tanaka et al, 2004;Zhang et al, 2005b) and the VDAC isoform VDAC3 (Rahmani et al, 2000;Kim, 2005).…”
Section: Hbxmentioning
confidence: 95%
“…HBx has been shown to affect apoptosis, signal transduction pathways, and oxidative stress through direct interactions with mitochondrial proteins (Lee et al, 2004). Upon the expression of HBx, there are increased levels of cellular ROS in hepatoma cell lines (Lee et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HBx is often found localized at the mitochondria [6][7][8]. HBx targeting to mitochondria causes a loss of mitochondrial membrane potential that has been linked to cell death [9] and oxidative liver injury [10]. In addition, mitochondria-associated HBx has been shown to activate signal transducer and activator of transcription 3 and nuclear factor kappa B (NF-κB) and induce mitochondrial translocation of Raf-1.…”
Section: Introductionmentioning
confidence: 99%